Costa Rica, the key - García Valverde, Orlando; Cisneros Gallo, Máximo ([San José, Costa Rica] : Videoteck, 1990)
Descripción de lugares históricos y turísticos de Costa Rica.
Documental--Créditos: Photography, Gerardo Leandro, Adalberto Blanco; editing, Rodrigo Chanto, José Gamboa, Ronald Castro; hosted by Máximo Cisneros, Rebecca Montagne
Keywords: COSTA RICA -- HISTORIA; COSTA RICA -- VIDA SOCIAL Y COSTUMBRES